'A Web of Community': Uncovering African American Historic Sites in Deerfield, MA. Issue 2 (18th May 2015) - Sesma, Elena
Abstract : In 2012, the Pocumtuck Valley Memorial Association published the 'Map and Guide to African American Historic Sites in Deerfield, Massachusetts'. The map provides information on 23 sites along the nearly mile-long street of Historic Deerfield, each of which is related to the story of free or captive Africans in the town's early history. As with the other case studies in this issue, the Deerfield Map and Guide operates as a trail in that it directs people through the town of Historic Deerfield while narrating a story about the early rural New England village. The map enables movement through the landscape of Deerfield and makes visible the history of slavery and race in a place that is so often associated with abolition and freedom. This paper discusses the process by which museum educators, historians, and academic and community advisors developed the map and guide in both digital and pamphlet form, including how information was collected and organized, and the intended goals of producing this material.